2015
DOI: 10.1159/000440848
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Retinal Vein Occlusion with Ranibizumab in Clinical Practice: Longer-Term Results and Predictive Factors of Functional Outcome

Abstract: Purpose: To evaluate long-term results and predictors of efficacy in patients with macular edema due to retinal vein occlusion (RVO) treated with intravitreal ranibizumab in a clinical practice setting. Methods: The clinical records of patients with a minimum follow-up of 3 years were retrospectively analyzed. Sixteen eyes with branch RVO (BRVO) and 16 with central RVO (CRVO) were included. All patients performed cross-sectional evaluation with best-corrected visual acuity (BCVA), spectral domain optical coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
(48 reference statements)
2
16
1
Order By: Relevance
“…Another study by Farinha and associates assessed predictors of functional outcomes in patients with BRVO treated with ranibizumab. Their study demonstrated that a better initial BCVA correlated with a better final BCVA, while RPE disruption negatively correlated with final BCVA 15. These results appear to be in conflict with the visual acuity findings in our study and the study by Kim and colleagues.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study by Farinha and associates assessed predictors of functional outcomes in patients with BRVO treated with ranibizumab. Their study demonstrated that a better initial BCVA correlated with a better final BCVA, while RPE disruption negatively correlated with final BCVA 15. These results appear to be in conflict with the visual acuity findings in our study and the study by Kim and colleagues.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worthy to mention that both ischemic and nonischemic CRVO types showed a positive response to anti-VEGF agents based on pivotal trials [12][13][14][15][16][17] . Real-life data also demonstrated significant anatomical and visual improvement in patients with CRVO treated with intravitreal anti-VEGF agents in a variable follow-up period [18][19][20] .…”
Section: Introductionmentioning
confidence: 80%
“…However, it is worthy of note that there is a lack of standardized definition for ischemia so far, and, therefore, there is controversy in the results of the studies regarding ischemia and its role in the visual outcome. Regarding the effect of retinal ischemia, Farinha et al [18] also demonstrated that ischemic eyes with RVO had larger final FAZ areas and worse functional outcome. This was in accordance with Sophie et al [23] , who stated that in patients with RVO retinal nonperfusion may contribute to restricted visual gain in the long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The management of macular edema secondary to branch retinal vein occlusion has greatly improved in recent times with the introduction of a therapy based on intravitreal injection of antivascular endothelial growth factor (VEGF) molecules and steroids [69]. Patient outcomes even with identical treatments can be vastly different due to disease, and patient heterogeneity prognostic factors for BRVO include patient age [70], baseline visual acuity and retinal thickness [51, 71, 72], early response to treatment [70], duration of macular edema [73, 74], posterior vitreous detachment [75], OCT characteristic [7678], cytokine level [34, 79], central retinal sensitivity [80], leaking capillaries and microaneurysms in the perifoveal capillary network [60, 81, 82], retinal pigment epithelium (RPE) integrity [83, 84], serious retinal detachment [85], and subretinal hemorrhage [86]. Some of these prognostic factors are still controversial.…”
Section: Treatmentmentioning
confidence: 99%